(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Loss of hearing power might be due to several reasons such as; old age, hearing loud sound that can damage the auditory system and so on. Hearing aid device is an elecronic system used to enhance weak sound signals to a level that those with different levels of partial hearing loss can hear. This paper considers the design and implimentation of a low cost hearing aid device.Design equations were employed to calculate the physical parameters of the different units of the circuit. The frequency response test showed a constant flat response from to about 2 at gain of the maximum current drawn by the device is per second. When tested on 4 people with partial hearing problem, the results showed that there was a significant improvement in the hearing ability of all the patients tested. The paper recommends that design of digital hearing aid be considered to enhance output signal quality and feedback control.